2013
DOI: 10.1016/j.pscychresns.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate system genes and brain volume alterations in pediatric obsessive-compulsive disorder: A preliminary study

Abstract: Obsessive-compulsive disorder (OCD) has been associated with regional volumetric brain abnormalities, which provide promising intermediate phenotypes of the disorder. In this study, volumes of brain regions selected for a priori evidence of association with OCD (orbitofrontal cortex (OFC), anterior cingulate cortex (ACC), thalamus, caudate, putamen, globus pallidus and pituitary) were measured using structural magnetic resonance imaging (MRI) in 20 psychotropic-naïve pediatric OCD patients. We examined the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 54 publications
(84 reference statements)
0
46
0
3
Order By: Relevance
“…SLC1A1 gene encodes a high-affinity excitatory amino acid transporter which is selectively expressed in the central nervous system. In contrast, Wu et al (2012) uncovered a trend between rs301430 in SLC1A1 and increased thalamic volume. Both observations might be caused by transcriptional alterations, because both variants lie in the 3 0 untranslated region of the SLC1A1 gene (Arnold et al, 2009a;Wendland et al, 2009).…”
Section: The Glutamatergic Systemmentioning
confidence: 85%
See 2 more Smart Citations
“…SLC1A1 gene encodes a high-affinity excitatory amino acid transporter which is selectively expressed in the central nervous system. In contrast, Wu et al (2012) uncovered a trend between rs301430 in SLC1A1 and increased thalamic volume. Both observations might be caused by transcriptional alterations, because both variants lie in the 3 0 untranslated region of the SLC1A1 gene (Arnold et al, 2009a;Wendland et al, 2009).…”
Section: The Glutamatergic Systemmentioning
confidence: 85%
“…Moreover, the NMDA receptors are thought to be involved in neurodevelopmental processes of the nervous system, as with the GRIN2B and GRIN2A (Endele et al, 2010;Hall et al, 2007). Although a meta-analysis by Taylor (2013) found no association between GRIN2B and OCD, imaging-genetic findings suggest that GRIN2B affects glutamatergic concentrations in the ACC of OCD patients (Arnold et al, 2009b), as well as volumes in the ACC, OFC (Arnold et al, 2009a), and thalamus (Wu et al, 2012). Moreover, a new candidate gene for OCD risk, which encodes DLGAP (SAPAP-related) (Bienvenu et al, 2009;Stewart et al, 2013b;Zü chner et al, 2009), was recently reported to affect ACC and OFC volume in OCD (Wu et al, 2012).…”
Section: The Glutamatergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…For the DLG4 gene, SNPs (Table 1) and CNVs (Table 3) have been identified only in patients with schizophrenia and with 84 Zanni et al 83 Philips et al 84 Kantojärvi et al 115,116 rs2301963 (associated with decreased orbitofrontal cortex white matter volume) 117 Chien et al 115 Li et al 116 Wu et al 125 Spellmann et al 122 Zhao et al 123 De Luca et al 124 Strauss et al autism-spectrum disorders, respectively. In contrast, SNVs have been associated with both disorders (Table 2).…”
Section: Protein Dlg4mentioning
confidence: 99%
“…Interestingly, glutamatergic candidate genes (DLGAP2) have shown a strong trend towards significant association with pre-frontal volumetric changes in a pediatric OCD sample (65), but further studies are required to establish the relationship between candidate genes and physiology of OCD. A recent whole genome association study found an association between OCD and DLGAP1, a member of the neuronal postsynaptic density complex.…”
Section: Genetic Familial and Environmental Factorsmentioning
confidence: 99%